Penggunaan Sudut Baca dalam Program Literasi Sekolah Dasar - Kharisma, Nova; Kironoratri, Lintang; Fakhriyah, Fina (Universitas Nusantara PGRI Kediri, 2025)
This study was conducted because there are still students of SDN 2 Bendanpete who are not yet fluent in reading. The school tries to improve student literacy by implementing a literacy program, and reading corners as one of the facilities used. The study aims to examine in depth the use of reading corner facilities by students of SDN 2 Bendanpete. The method used is descriptive qualitative. Data collection is carried out through observation, interviews, and documentation. Data analysis through data reduction, data presentation, and conclusions. In the lower grades, students have not been able to carry out proper maintenance and misuse the facilities so that there is damage to the physical condition of the reading corner which causes the use of these facilities to not be carried out optimally. While students in the upper grades are already able to carry out proper maintenance and use so that the physical condition of the reading corner in the upper grades is still very good and the use of the reading corner can be carried out optimally.